The Intellectual Legacy of Sheikh Yasin al-Fadani in Hadith Studies - Faisal Amri Al-Azhari (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to examine Sheikh Yasin al-Fadani within the discipline of Hadith sciences. As a Nusantara scholar who was active in Makkah during the 20th century, Sheikh Yasin played a significant role in maintaining the integrity and continuity of the sanad, which is a fundamental aspect of Islamic tradition and Hadith authentication. Through a systematic literature review of his works, articles, books, and other relevant primary sources, this study highlights Sheikh Yasin’s methodological rigor and scholarly impact. The findings reveal that his dedication to collecting sanad produced one of the most comprehensive chains of transmission still referenced today, thereby contributing to the sustainable preservation of Islamic scholarly heritage.